A comparison of food‐based decision‐making between restricting and binge‐eating/purging subtypes of anorexia nervosa. Issue 10 (12th August 2020) - Uniacke, Blair; Slattery, Reile; Walsh, B. Timothy; Shohamy, Daphna; Foerde, Karin; Steinglass, Joanna
Abstract: Objective: By definition, restricting (ANR) and binge‐eating/purging (ANBP) subtypes of anorexia nervosa (AN) differ in some manifestations of maladaptive eating behavior. This study aimed to determine whether the groups differ in the choices they make about what to eat, and whether there are differences in valuation related to food choice, using an experimental paradigm. Method: Inpatients with ANR ( n = 40) and ANBP ( n = 46) participated in a Food Choice Task. During the task, participants rated 76 food images for healthiness and tastiness, and choice preferences. Groups were compared in percent selection of high‐fat and low‐fat foods, value ratings of foods, and engagement of self‐control in food choice. Results: There were no differences between AN subtypes in healthiness or tastiness ratings, or in tendency to limit choice of high‐fat foods. There was no difference between the groups in measures of self‐control in food choice. Discussion: Individuals with ANR and ANBP similarly manifest reduced choices of high‐fat foods, with similar tendencies to undervalue the tastiness of high‐fat foods. These results suggest that while individuals with ANR and ANBP differ across a range of clinical characteristics, the decision‐making process associated with the maladaptive restriction of high‐fat foods characteristic of AN is shared by both subtypes.